IL-25/IL-33–responsive TH2 cells characterize nasal polyps with a default TH17 signature in nasal mucosa - Lam, Emily P.S.; Kariyawasam, Harsha H.; Rana, Batika M.J.; Durham, Stephen R.; McKenzie, Andrew N.J.; Powell, Nicholas; Orban, Nara; Lennartz-Walker, Melissa; Hopkins, Claire; Ying, Sun; Rimmer, Joanne; Lund, Valerie J.; et al. (Journal of allergy and clinical immunology, 2016)
Chronic rhinosinusitis with nasal polyposis (CRSwNP) in Western countries is characterized by eosinophilia, IgE production, and TH2 cytokine expression. Type 2 innate lymphoid cells from polyps produce IL-5 and IL-13 in response to IL-25 and IL-33, although the relevance of this axis to local mucosal T-cell responses is unknown. We sought to investigate the role of the IL-25/IL-33 axis in local mucosal T-cell responses in patients with CRSwNP. Polyp tissue and blood were obtained from patients undergoing nasal polypectomy. Control nasal biopsy specimens and blood were obtained from healthy volunteers. Tissue was cultured in a short-term explant model. T-cell surface phenotype/intracellular cytokines were assessed by means of flow cytometry. T-cell receptor variable β-chain analysis was performed with the immunoSEQ assay. Microarrays were performed for gene expression analysis. IL-25 receptor (IL-17RB)–expressing TH2 effector cells were identified in nasal polyp tissue but not the healthy nasal mucosa or periphery. IL-17RB+CD4+ polyp–derived TH2 cells coexpressed ST2 (IL-33 receptor) and responded to IL-25 and IL-33 with enhanced IL-5 and IL-13 production. Within IL-17RB+CD4+ T cells, several identical T-cell receptor variable β-chain complementarity-determining region 3 sequences were identified in different subjects, suggesting clonal expansion driven by a common antigen. Abundant IL-17–producing T cells were observed in both healthy nasal mucosal and polyp populations, with TH17-related genes the most overexpressed compared with peripheral blood T cells. IL-25 and IL-33 can interact locally with IL-17RB+ST2+ polyp T cells to augment TH2 responses in patients with CRSwNP. A local TH17 response might be important in healthy nasal mucosal immune homeostasis.